PENGARUH LATIHAN TARGET MENGGUNAKAN GAWANG KECIL DAN BAN BEKAS TERHADAP AKURASI SHOOTING PEMAIN FUTSAL SMAN 4 LUWU - Juniarta, Teguh; Ahmad; A. Heri Riswanto; Hidayat, Rachmat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted due to the fact that many futsal players at SMAN 4 Luwu still have inconsistent shooting accuracy. Therefore, this study focuses on target training aimed at improving the shooting accuracy of the futsal players at SMAN 4 Luwu. The researcher employed a quasi-experimental method. Data collection was carried out by administering pre-tests and post-tests. The population in this study consisted of 40 individuals, with a sample size of 20. The sample was selected using cluster random sampling and then divided into two groups: ten individuals trained using small goals, and ten using used tires.The research results show that the t-count value in experimental group 1 (used tires) is 0.035 and in experimental group 2 (small goals) is 0.017, both of which are higher than the 5% significance level (0.05), (0.035 > 0.05) & (0.017 > 0.05). Therefore, the accuracy of futsal goal shots by SMAN 4 Luwu players is influenced by training using small target goals and used tires. The mean score of experimental group 1 with small goals is higher than that of experimental group 2 with used tires (14.80 > 14.50). It can be concluded that for SMAN 4 Luwu futsal players, training with small goals is more effective than with used tires.